Pluralisme Hukum di Era Desentralisasi: Resolusi Konflik Normatif Awig-Awig dan Tata Hukum Nasional di Lombok - Anies Prima Dewi; Syaryanti Hussin (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2026)
The existence of legal pluralism in Indonesia often triggers tension between the centralistic national legal system and localized customary law (hukum adat), particularly in the era of decentralization. This article analyzes the constitutionality and binding force of Awig-Awig (written and unwritten customary rules) within the Sasak community in Lombok, and offers an integrative normative conflict resolution model. Through a normative legal research method employing statutory and conceptual approaches, this study finds that although Article 18B of the 1945 Constitution guarantees the unity of customary law communities, the juridical recognition of Awig-Awig is frequently hindered by the prerequisite "as long as it remains in existence and is in accordance with societal development." Normative conflicts frequently occur at the level of communal sanctions and public policy, including in the aspects of public order and community health regulations. The research results indicate that the sociological binding force of Awig-Awig is significantly stronger than its juridical binding force. Therefore, this article proposes an "Integrative Normativization" model, wherein local wisdom is transformed into Village Regulations (Peraturan Desa/Perdes) to provide legal certainty without diminishing the philosophical values of the local community.